Use of conditioning regimen and antiviral central memory cd8 + anti-suppressive cells for haploid identical stem cell transplantation - REISSNER, JARL; BAHAR-LUSTIG ESTHER (2025)
Provided is the use of a conditioning regimen antiviral central memory CD8 + anti-suppressive cell in stem cell transplantation of haploid identity. Accordingly, a method of treating a disease in a subject in need thereof is provided, where the disease includes pathological cells present in the bone marrow of the subject. The method comprises: conditioning the subject under a pre-transplantation conditioning regimen comprising total bone marrow irradiation; immature hematopoietic cells depleted by T cells are transplanted into the body of the subject; administering a cyclophosphamide to the subject; and administering the anti-non-graft versus host disease inducing cell to the subject. 提供了调理方案抗病毒中央型记忆CD8+反抑细胞用于单倍体相同的干细胞移植中的用途。因此，提供了一种治疗有此需要的受试者中的疾病的方法，其中疾病包括存在于受试者骨髓中的病理性细胞。该方法包括：在包含全骨髓照射的移植前调理方案下调理受试者；将T细胞耗尽的未成熟造血细胞移植到所述受试者体内；向受试者施用环磷酰胺；和向受试者施用反抑非-移植物抗宿主病诱导细胞。